Analysis of obstetric complications reported to the National Patient Insurance Association in Finland from 1987 to 1995 - Tapio Kurki (Acta Obstetricia et Gynecologica Scandinavica)
Background. The launch of the National Patient Insurance Association in 1987 off erred a good starting point to evaluate obstetric claims in Finland. In order to obtain full compensation after patient injury, proof of malpractice is no longer required. Thus, the register of the Association offers a solid data base to analyze these injuries. Methods. A nationwide descriptive study of obstetric claims reported to the National Patient Insurance Association from 1.5.1987 to 31.12.1995. The recorded statistical datafiles of the Association were used in the analysis. Results. A total of 801 obstetric claims were analyzed. This comprised 2% of all (n = 39189) claims during the same time period. Nearly all injuries leading to claims (683/801, 85%) occurred during delivery. In all, 156 (19.5%) claims resulted in compensation. The total sum of compensation paid was $ 1.3 million. Most often (30/80 37.5%) and highest compensation ($ 0.8 million) was paid due to delay in the diagnosis of fetal asphyxia. In all, 118 (0.3%) malpractice trials in court have arisen from all claims to the Association during the study period; only two (1.7%) resulted from obstetric causes. Conclusions. The data indicate that most common and serious obstetric complications are associated with delay in the diagnosis of fetal asphyxia. Thus, from both the legal and the medical points of view, pertinent fetal monitoring during delivery and umbilical artery blood gas analysis after delivery in all risk deliveries should be obligatory in all delivery units. Finally, and perhaps most importantly, the patient insurance has effectively prevented obstetric malpractice trials in court.